Supernatural agents and prosociality in historical China: micro-modeling the cultural evolution of gods and morality in textual corpora. Issue 1 (2nd January 2021) - Nichols, Ryan; Slingerland, Edward; Nielbo, Kristoffer Laigaard; Kirby, Peter; Logan, Carson
ABSTRACT: A major source of attention paid to high gods in the fields of cultural evolution and cognitive science is the social effects of belief in high gods. Belief in high gods is both hypothesized to catalyze a cognitive punishment-avoidance mechanism at the level of individual minds, and a group cultural evolutionary mechanism that amplifies in-group cooperation. Recent research into non-Western contexts not only indicates a multiplicity of supernatural influences on the individual-level and group-level mechanisms but raises questions about theoretical presuppositions about how a supernatural agent is classified as a high god or as something else. Our exploratory study operationalizes the question "Does historical China have high gods?" through the assessment of semantic associations between each of several supernatural agent categories (alleged high gods, low gods, ancestors, sage kings, and emperors) and each of several social functional content categories (punishment, reward, morality, monitoring, and religion). Analyzing collocations in a corpus of 5.7 m Chinese characters, representing all of the most influential historical Chinese-language texts, our preliminary results suggest social functions of supernatural agents in historical China were widely distributed across many species of supernatural agent thereby complicating a claim that high gods constitute a special category in relation to these social functions.